Investigating Students’ Voices towards Online Writing Class in Vocational High School Context - Mutiara Ayu; Kianna Joy Christie (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2023)
Nowadays, online learning that is conducted by students requires them to work harder to carry out the learning process. It is undeniable that students at various levels of education have used online platforms to help the learning process, including vocational high school students. Therefore, it is interesting to investigate students' voices about the implementation of online classes in their schools. In this study, researchers focused on the use of Google Classroom among vocational school students attending online writing classes. This study uses a case study design by selecting eighty students in Bandar Lampung. To collect data, researchers distributed questionnaires through Google Forms and interviewed students. The results showed that students had positive and negative perceptions about the implementation of Google Classroom, namely: (1) There are issues with connecting Google Classroom to the internet; (2) Students do not comprehend the writing materials provided by Google Classroom; and (3) Students' laziness and lack of discipline in carrying out or collecting assignments (5) Students have difficulty expressing themselves and responding in the writing class via Google Classroom. Furthermore, several challenges were discovered for students in online writing classes via Google Classroom, including: (1) Student indiscipline due to being too bored to do online assignments; (2) students' lack of understanding of writing material in class; and (3) Students' lack of interaction with teachers in Google Classroom.